An introduction to the world's oceans - Duxbury, Alyn C.; Duxbury, Alison B. (Dubuque, IA : Wm.C. Brown Publishers, 1991)
Environment Management
Keywords: Oceans; Oceanography; Water planet; Sea floor; Salt water; Life